Evaluation of modified Vaccinia Ankara-based vaccines against foot-and-mouth disease serotype A24 in cattle. Issue 4 (22nd January 2020) - Steigerwald, Robin; Brake, David A.; Barrera, José; Schutta, Christopher J.; Kalla, Markus; Wennier, Sonia T.; Volkmann, Ariane; Hurtle, William; Clark, Benjamin A.; Zurita, Mariceny; Pisano, Melia; Kamicker, Barbara J.; et al.
Highlights: FMDV P1 and 3C expression levels optimized for vaccine production in CEF cells. Correct FMDV P1 antigen expression and processing in bovine cells. MVA-BN-FMD vaccines were 100% efficacious against FMDV homologous challenge. Cattle had relatively low FMDV serum neutralizing antibody titers but no disease. MVA-BN-FMD vaccines did not require an adjuvant to confer full protection. Abstract: To prepare foot-and-mouth disease (FMD) recombinant vaccines in response to newly emerging FMD virus (FMDV) field strains, we evaluated Modified Vaccinia virus Ankara-Bavarian Nordic (MVA-BN®) as an FMD vaccine vector platform. The MVA-BN vector has the capacity to carry and express numerous foreign genes and thereby has the potential to encode antigens from multiple FMDV strains. Moreover, this vector has an extensive safety record in humans. All MVA-BN-FMD constructs expressed the FMDV A24 Cruzeiro P1 capsid polyprotein as antigen and the FMDV 3C protease required for processing of the polyprotein. Because the FMDV wild-type 3C protease is detrimental to mammalian cells, one of four FMDV 3C protease variants were utilized: wild-type, or one of three previously reported mutants intended to dampen protease activity (C142T, C142L) or to increase specificity and thereby reduce adverse effects (L127P). These 3C coding sequences were expressed under the control of different promoters selected to reduce 3C protease expression. Four MVA-BN-FMD constructs were evaluated in vitro for acceptable vector stability, FMDV P1 polyprotein expression, processing, and the potential for vaccine scale-up production. Two MVA-BN FMD constructs met the in vitro selection criteria to qualify for clinical studies: MVA-mBN360B (carrying a C142T mutant 3C protease and an HIV frameshift for reduced expression) and MVA-mBN386B (carrying a L127P mutant 3C protease). Both vaccines were safe in cattle and elicited low to moderate serum neutralization titers to FMDV following multiple dose administrations. Following FMDV homologous challenge, both vaccines conferred 100% protection against clinical FMD and viremia using single dose or prime-boost immunization regimens. The MVA-BN FMD vaccine platform was capable of differentiating infected from vaccinated animals (DIVA). The demonstration of the successful application of MVA-BN as an FMD vaccine vector provides a platform for further FMD vaccine development against more epidemiologically relevant FMDV strains.